Clinical cancer prevention - Senn, Hansjèorg; Otto, Florian (Recent results in cancer research, 2011)
This book is based on presentations by some of the world?s leading experts at the Sixth International Conference on Clinical Cancer Prevention, held in St. Gallen, Switzerland, during March 2010. The main themes are the latest advances in the prevention of breast and prostate cancer and the role of infection in the development of liver and gastric cancer. Special emphasis is given to perspectives on the chemoprevention of breast cancer, as the conference included an international consensus meeting on this subject. New research findings are presented and potentially more effective cancer prevention strategies are discussed, with careful consideration of controversies. The expertise of the contributors encompasses genetics and microbiology, epidemiology, and health economics, as well as clinical cancer prevention. This book will be of interest to all who wish to learn about the most recent progress in combating the development of cancer.